Identifikasi Gulma Resisten Herbisida Paraquat Pada Lahan Jagung di Kecamatan Tigabinanga Kabupaten Karo - Kristian Adinata Ginting; Edison Purba; Jonis Ginting (Jurnal Agroekoteknologi, 2015)
Paraquat is a herbicide commonly used for weed control in corn fields at Tigabinanga Subdistrict(TS), Karo District North Sumatera.The aim of this research was to identify paraquat resistant weedspecies (Echinochloa colonum and Eleusine indica) in corn fields at TS. This research consist of 3steps: seed collection, screening of paraquat resistant weed biotypes, and dose response test. Seed ofputative paraquat resistant biotypes were randomly collected from 28 corn fields in TS. Atscreening test, paraquat at the rate of 150 g a.i./ha was evaluated against weed populations to findresistant and susceptible biotypes. The experiment was performed in a randomized block designwith three replications. Dose response test was arranged in a randomized block design and fourreplications with eight levels of paraquat dose (0, 25, 50, 100, 200, 400, 800, 1600 g a.i./ha). Theresults showed that none of E. colonum TS population was resistant to paraquat whereas E. indicaTS populations were 2 population resistant, 4 population moderate resistant, and 21 populationsusceptible to paraquat. Resistant index of Benjire Village (ETB-14) and Perlamben Village (ETB-19) biotype were >5 and >9 times of susceptible population.Key words: paraquat-resistant, E. colonum, E. indica